Pengaruh Model Pembelajaran Problem Based Learning dengan Media Jam Pecahan terhadap Hasil Belajar Siswa - Setyoningsih, Suci; Rahmawati, Noviana Dini; Martatik (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to analyze and prove the effect of using the Problem Based Learning (PBL) learning model with fractional hour media on the mathematics learning outcomes of fractional material in grade IV students of SDN Pandeanlamper 03 before and after the action. This research design uses pre-experimental designs with saturated sample techniques so that the sample used is 28 students. Then the results of the study were obtained from data collection in the form of observation, documentation, pretest and posttest written tests. So that the results of research that the use of the problem-based learning model with fractional hour media affects student learning outcomes. This is proven by the n-gain test result of 0.5686 which means that the use of this model is quite effective with moderate criteria. Then test the hypothesis with the sig value. (2-tailed) of 0.000 < 0.05 or a calculated value of 8.043 > table 2.051, then the basis for decision making can be concluded that H0 is rejected or Ha is accepted which means that there is an influence of the Problem Based Learning (PBL) learning model with fractional hour media on student learning outcomes.